O uso de princípios de metodologias ativas em oficina de formação continuada e integração de equipes sociopsicopedagógicas da assistência estudantil das IFES - NASCIMENTO, Adriana Maria Gomes do (Universidade Federal do Pará, 2023)
This dissertation reports a professional master's research in the area of Teaching. It is composed by a theoretical-methodological part that guides the research and the other discusses the proposal of the study that we developed and resulted in the educational product, proposal for the structure of a continuing education workshop for the sociopsychopedagogical team of student assistance. The general objective of the study was the development of a creative and innovative educational instrument that could foster the process of continuous and integrated training of social workers, psychologists and pedagogues who are part of sociopsychopedagogical teams, who work in student assistance at federal institutions of higher education. The proposal arose from preliminary bibliographic studies that found the lack of materials and guidelines that could contribute to the orientation of the work carried out by the sociopsychopedagogical teams, since it is still considered a relatively new area of activity. For this purpose, the main conceptual axes used were: principles of active methodologies; educational instruments and technologies; meaningful learning; continuing education and integration; creativity and; innovation. The product proposal consisted of carrying out a workshop with a multidisciplinary team that works at the Student Assistance Superintendence - SAEST of the Federal University of Pará - UFPA. In the methodology, the research site and the resources needed to carry out the workshop were detailed, which was carried out in a remote format, so that it could meet both the norms of social isolation due to the New Coronavirus pandemic and facilitate the participation of professionals that work in Student Assistance on the UFPA campuses, which are located in the interior of Pará. Each hour of 30 hours was divided into: asynchronous activities and three synchronous meetings. The workshop, based on the principles of active methodologies, enabled professional reflection in a teaching-learning context, where it can be negotiated and discussed dialogically among the senses, arguments, positions, thoughts, which contribute to the process of personal construction and interpersonal of the team, based on the multiplicity of versions on the themes addressed chosen by the participants themselves. Although this educational product cannot solve all the training and integration problems of socio-psycho-pedagogical teams on its own, it proved itself capable, during the pilot test, of contributing to the teaching-learning process, in the construction and in the strengthening of knowledge, through reflections on professional practices and which roles currently circumscribe Student Assistance. It should be noted that the product has the potential for germination and can be applied to other training contexts that have objectives similar to those indicated in this study, provided that the necessary adaptations are made.